Analysis of The Influence of Enterprise Risk Management Implementation on Company Performance and Company Value - Maharani, Clarissa; Efa Yonnedi (Jurnal Akuntansi, 2023)
This study aims to explore the degree to which the implementation of enterprise risk management (ERM) affects company performance and value. Assessing the level of ERM implementation is done by using six components derived from governance and firm operating activities. This study also used board of directors, firm size, leverage and return on equity (ROE) as control variables. The population in this study include Technology, Infrastructure, transportation and logistic sector listed on the Indonesia Stock Exchange from 2018 to 2020. Samples were taken using purposive sampling method which amounted to a total of 52 companies. The result of the first model shows that financial performance of ROA, ERM Implementation, Leverage, Return on Equity, BODSIZE and Firm Size variable effect simultaneously. But ERM Implementation only partially influences ROA. In measuring Firm Value of Tobin’s Q, the effect of ERM implementation, BODSIZE, Size, Leverage and ROE were assessed simultaneously. On the other hand, ERM implementation and BODSIZE only partially impact Tobin’s Q.